2011
DOI: 10.1097/iae.0b013e318206cf1c
|View full text |Cite
|
Sign up to set email alerts
|

A Restudy of the Surgical Anatomy of the Posterior Aspect of the Globe

Abstract: The horizontal meridian (foveal horizontal meridian), defined by the entry site and course of the long posterior ciliary arteries, serves as an important surgical landmark if precise external scleral buckling of the fovea is the objective. For practical purposes, foveal horizontal meridian, geometrical horizontal meridian, and optic nerve horizontal meridian need to be distinguished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The average distance in our study was 4.28 6 1.29 mm, which is greater than that reported. 6,17 However, our measurements were possible in only 58 eyes whose intrascleral entry of LPCAs and optic nerve sheath were detected clearly in the same OCT scan. To analyze the spatial relationship between the intrascleral entry of the LPCA and optic nerve, we needed to examine 3D images and reconstruct the images to show clearly the spatial relationship between the entry site of the LPCAs and optic nerve sheath in the same section.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The average distance in our study was 4.28 6 1.29 mm, which is greater than that reported. 6,17 However, our measurements were possible in only 58 eyes whose intrascleral entry of LPCAs and optic nerve sheath were detected clearly in the same OCT scan. To analyze the spatial relationship between the intrascleral entry of the LPCA and optic nerve, we needed to examine 3D images and reconstruct the images to show clearly the spatial relationship between the entry site of the LPCAs and optic nerve sheath in the same section.…”
Section: Discussionmentioning
confidence: 93%
“…Earlier histologic studies showed that the lateral LPCAs entered the sclera 3.9 mm temporal to the optic nerve, 17 and Siam et al 6 recently reported that the mean distance between the intrascleral entry of temporal LPCA and the optic nerve sheath was 3.0 mm in 12 human cadaver eyes. The average distance in our study was 4.28 6 1.29 mm, which is greater than that reported.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The long PCAs mainly supply a segment of the iris, ciliary body, and peripheral choroid on each side, respectively, whereas the short PCAs provide blood supply for both the ONH and the choroid. 29,30 We applied the same arterial blood pressure at these 18 nodes, and such pressure was allowed to vary between 70.8 and 93 mm Hg to mimic diastolic and systolic changes of the ophthalmic artery pressure. 31 In addition, a constant blood pressure of 15 mm Hg was applied at four nodes where the vortex veins leave the choroid (typically one in each quadrant) to drain the blood out of the choroid.…”
Section: Loading Conditionsmentioning
confidence: 99%
“…3D schematic showing the posterior portion of the eye globe and the blood vessels (vortex veins and posterior ciliary arteries) that pass through the posterior sclera and connect with the choroid (as described in the literature30 ).…”
mentioning
confidence: 99%